Risk Factors Associated with Unconjugated Neonatal Hyperbilirubinemia in Malaysian Neonates - Wong, FL; Boo, N; Othman, A (Oxford Univ Press, 2024)
Methods: A prospective study was conducted to investigate the effects of glucose-6-phosphate dehydrogenase (G6PD) mutation, variant uridine diphosphate glucuronosyltransferase UGT1A1 gene and hepatic organic anion transporter protein (OATP2) gene on a group of neonates. Hyperbilirubinemia was defined as a total serum bilirubin level of epsilon 250 mu mol/l. Results: Of 318 neonates, 52 (16.4%) had hyperbilirubinemia. The incidence of G6PD mutation was 5.4% (15/280) among these infants. The incidence of G6PD mutation was significantly higher in the male neonates with hyperbilirubinemia (7.8%) when compared with the normal male neonates without hyperbilirubinemia (1.8%; p = 0.03). Logistic regression analysis showed that the significant risk factors for neonatal hyperbilirubinemia were Malay ethnicity [adjusted odds ratio (OR), 2.77; 95% confidence interval (CI): 1.31-5.86; p = 0.007] and G6PD mutation (adjusted OR, 3.29; 95% CI: 1.06-10.1820; p = 0.039). The gender, birth weight and gestation age of neonates, variant c.211G > A and variant of OATP2 gene were not significant. Conclusions: Neonates with Malay ethnicity and G6PD mutation were at risk for hyperbilirubinemia.